Pengaruh Bauran Pemasaran Terhadap Minat Beli Konsumen Di Toko Almira Parfum - Sayekti, Levia Inggrit; Latifah, Tipa (JURNAL ILMIAH M-PROGRESS, 2025)
This study aims to analyze the effect of marketing mix consisting of product, price, location, and promotion on consumer purchasing interest at Almira Parfum Store, Lamongan. The background of this study is based on the increasing competition in the refill perfume industry and the importance of marketing strategies to attract consumer interest. This study uses a quantitative method with a survey approach. Data were obtained through questionnaires distributed to 220 respondents and analyzed using multiple linear regression with the help of SPSS software. The results of the study indicate that product, price, location, and promotion variables simultaneously influence consumer purchasing interest. Partially, price and location variables have a significant influence on purchasing interest, while the most dominant variable influencing consumer purchasing interest is promotion. This study provides practical implications for Almira Parfum Store to focus more on its marketing strategy, especially in terms of promotion and competitive pricing.